Study of Some Prophetic Hadiths That Are the Basis of the Conceptualization of Education (Analysis Study of Educational Hadiths) - Quthratun Nada, Ana; Shaleh; Alfikri, Adam Wildan (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
The position of Hadith in Islamic Religious Education is the basis and basis for the concept, framework and design of Islamic religious education, considering that Hadith provides more concrete reasons regarding the implementation of various activities that must be developed in Islamic life and the framework of life. The concept of Islamic education in the review of educational hadith includes: basic education, learning obligations, educational goals, educational institutions, educational materials (tarbiyyah), learning methods, educators (teachers), pupils (students), women's education, and learning assessment. All of this is the basic framework for building Islamic religious education in accordance with the Hadith of the Prophet